Impact of a Provincial Asthma Guidelines Continuing Medical Education Project: The Ontario Asthma Plan of Action's Provider Education in Asthma Care Project. Issue 2 (2007) - Lougheed, M Diane; Moosa, Dilshad; Finlayson, Shelagh; Hopman, Wilma M; Quinn, Mallory; Szpiro, Kim; Reisman, Joseph
Abstract : BACKGROUND: The Ontario Ministry of Health and Long-Term Care funded the Ontario Lung Association to develop and implement a continuing medical education program to promote implementation of the Canadian asthma guidelines in primary care. OBJECTIVES: To determine baseline knowledge, preferred learning format, satisfaction with the program and reported impact on practice patterns. METHODS: A 3 h workshop was developed that combined didactic presentations and small group case discussions. Outcome measures included a workshop evaluation, baseline assessment of asthma management knowledge and three-month postreflective evaluations. RESULTS: One hundred thirty-seven workshops were delivered to 2783 primary care providers (1313 physicians, 1470 allied health) between September 2002 and March 2005. Of the 2133 participants, 1007 physicians and 1126 allied health professionals submitted workshop evaluations. Most (98%) of the attendees indicated they would recommend the workshop to a colleague. The majority preferred the combination of didactic lecture plus interactive case discussions. A subset of physicians provided consent to use these data for research (n=298 pediatric and 288 adult needs assessments; n=349 postreflective evaluations). Important needs identified included appropriate medication for chronic asthma and development of written action plans. On the postreflective evaluations, 88.7% remained very satisfied, 95.5% reported increased confidence, 91.9% reported an influence on practice and 67.2% reported using a written action plan. CONCLUSIONS: This continuing medical education program addresses identified needs of primary care providers. Participants reported improvements in asthma care, including prescribing practices, use of spirometry and written action plans. Similar programs should be considered as part of multifaceted asthma guidelines dissemination and implementation initiatives in other provinces and nationally.